Rhenium(I) tricarbonyl complexes with 4,4´´-azobis(2,2´-bipyridine) - Abate, Pedro Oscar (2016)
Rhenium(I) tricarbonyl complexes have interesting optical and electrical properties that can be applied in the design of molecular devices.1 We describe in this work the synthesis and spectroscopic and electrochemical characterization of new Re(I) species of formula: [{Re(CO)3Cl}2L] , 1 and [{Re(CO)3(CH3CN)}2L](PF)6 , 2 , where L = 4,4??-azobis(2,2?-bipiridine, whose structure is shown in Scheme 1. The IR spectrum of complex 2 shows the typical stretching frequencies CO at higher values than those of complex 1, which can be attributed to the competition between CH3CN and the CO groups for the metal electronic density. This effect is consistent with the shift observed in the absorption maxima corresponding to the MLCT d(Re) *(L) bands in the UV-Visible spectra for both species in CH3CN: max = 450 nm for 1 and max = 380 nm for 2. By adding L-cysteine to complex 2 (at pH = 7.5), the lowest-energy MLCT band is displaced to higher energiesmax = 350 nm), thus pointing to a reduction of the azo group. This colour change can be applied for sensing aminoacids. On the other hand, by irradiating complex 2 at ex = 277 nm for 1 hour, the shifts in the UV-visible bands to higher energies disclose a trans-cis isomerization process, sensitized by a low-energy MLCT state.In conclusion, complex 2 can be used as a molecular switch for sensing biologically relevant compounds and as a model for controlling changes of molecular geometry induced by light.